Comparison of The Makeup Process Starting from Eyebrows and Complexion on the Final Results in Nusantara Bridal Practice Activities of UNESA Makeup Students Class of 2023 - Fadia Lailatil Aghna; Sri Usodoningtyas; Biyan Yesi Wilujeng; Dindy Sinta Megasari (Universitas Negeri Surabaya, 2025)
Bridal makeup is an activity of facial makeup on the bride that aims to highlight the existing advantages and cover up facial deficiencies. In the bridal makeup process, makeup artists generally use makeup techniques starting from the eyebrows and starting from Complexion. The purpose of this study is to determine the efficiency, disadvantages, advantages, and standards of good makeup work results. This type of research is quantitative, with a data collection method using a questionnaire sheet with a total of 159 respondents from UNESA Makeup Students. The data analysis method used is the independent sample t-test statistical test using the SPSS program. The results of this study are that the makeup technique starting from the eyebrows has a value of all aspects of 23.1195 and the average calculated value of all aspects of the statement is 2.889, the makeup technique starting from Complexion has a value of all aspects of 22.679 and the average calculated value of all aspects of the statement is 2.834, and there is a significant difference between the makeup process from the eyebrows and the makeup process from Complexion. The average difference between the two groups was 0.912 with a Standard Error of 0.437. This study shows that although both techniques have their own advantages, the technique of starting from the eyebrows is more recommended for a more efficient makeup process